A perspective on mental health literacy and mental health issues among Australian youth: Cultural, social, and environmental evidence! - Hirukshi Bennett; Ben Allitt; Fahad Hanna; Fahad Hanna (Frontiers Media S.A., 2023)
Mental health literacy (MHL) helps improve mental health outcomes and reduce the impacts of mental illness. This study aims to reflect on scientific evidence on MHL levels, barriers to MHL, their impacts on mental health among Australian youth and interventions to overcome these barriers. The factors explored in the Perspective included; influence of social determinants, culturally and linguistically diverse (CALD) communities, help-seeking attitudes and behaviors. MHL intervention programs and MHL for improving mental health outcomes due to the recent COVID-19 pandemic were also explored. Adequate levels of youth MHL significantly improved one's ability to recognize own mental health status as well as provide peer support. Practical considerations such as designing more gender and culturally specific youth MHL programs are proposed.